EP 30. Hybrid-H215O-PET-fMRI measures during galvanic vestibular stimulation. Issue 9 (September 2016) - Becker-Bense, S.; Stephan, T.; Albert, N.; Brendel, M.; Unterrainer, M.; Xiong, G.; Mille, E.; Habs, M.; Herz, M.; Schwaiger, M.; Dieterich, M.; Bartenstein, P.
Abstract : Background: Functional imaging studies on the central vestibular system by fMRI and H2 15 O-PET in healthy volunteers revealed similarities and differences in cortical activation patterns (Bense, 2001; Dietrich, 2003; Stephan, 2005; Stephan, 2009; Becker-Bense, 2014 ). These are ascribed to different experimental procedures and techniques. Whereas PET maps cerebral blood flow, fMRI measures changes of blood oxygenation via magnetic susceptibility changes.Galvanic vestibular stimulation (GVS) is applicable inside PET and MRI; it induces a perception of apparent self-motion mainly at onset (Stephan, 2009 ). Aim of the current study was to design a protocol for simultaneous PET-MRI of the vestibular system in order to compare the activation patterns between the two methods providing additional information for a deeper insight into the different mechanisms and improve the interpretation of the data. Methods: Six simultaneous PET-MRI scans were acquired in a hybrid scanner in nine healthy volunteers. During the stimulation scans AC-GVS was applied at 1 Hz (Stephan, 2005 ) with eyes closed (Fig. 1 ). FMRI EPI sequences were measured over 260 s. Dynamic PET acquisition started with injection of 750 MBq H2 15 O in a semibolus technique simultaneously with fMRI. Statistical direct comparison of PET and fMRI data were performed (paired t-test, SPM8). Results: MRI: Onset-related activation was seen of the multisensory vestibular cortical network and ocular motor areas bilaterally, as well as of premotor area BA 6 (SMA). Block-related activation represented a subset of this activation pattern without SMA activation. PET: The PET data of the first stimulation blocks revealed prominent activation of the SMA and cerebellar vermis. MRI vs PET: Paired comparison showed significantly stronger SMA PET signals compared to block-related MRI that was not present for onset-related MRI. Conclusions: The proposed procedure is suitable for direct statistical comparison of H2 15 O-PET and fMRI activations during vestibular stimulation. At comparable spatial resolution, the higher temporal resolution of fMRI can be utilized to interpret the simultaneous PET data in another context. On the other hand, the quantitative nature of the PET data can augment the fMRI data that provide only an indirect measure of cortical processing. The most different effects were seen in the SMA, where the PET signal seems to reflect the onset-related MRI signal due to self-motion perception which is most prominent at stimulus onset causing a preparatory motor response.